2017
DOI: 10.1098/rspb.2017.1883
|View full text |Cite
|
Sign up to set email alerts
|

Sleep macrostructure is modulated by positive and negative social experience in adult pet dogs

Abstract: The effects of emotionally valenced events on sleep physiology are well studied in humans and laboratory rodents. However, little is known about these effects in other species, despite the fact that several sleep characteristics differ across species and thus limit the generalizability of such findings. Here we studied the effect of positive and negative social experiences on sleep macrostructure in dogs, a species proven to be a good model of human social cognition. A non-invasive polysomnography method was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 67 publications
3
41
1
Order By: Relevance
“…Thus, for Study II, we analysed the ECG channel of polysomnography recordings conducted after a short positive versus a negative dog–human social interaction (see later). The original study [ 49 ] found that sleep macrostructure was markedly different between pre-treatment conditions, with a shorter sleep latency after the negative social interaction and a redistribution of the time spent in the different sleep stages. However, changes in cardiac activity have not been investigated in this context.…”
Section: Study IImentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, for Study II, we analysed the ECG channel of polysomnography recordings conducted after a short positive versus a negative dog–human social interaction (see later). The original study [ 49 ] found that sleep macrostructure was markedly different between pre-treatment conditions, with a shorter sleep latency after the negative social interaction and a redistribution of the time spent in the different sleep stages. However, changes in cardiac activity have not been investigated in this context.…”
Section: Study IImentioning
confidence: 99%
“…Dogs were not trained for the purpose of this experiment. (Note that originally N = 16 dogs participated in this experiment [ 49 ], however the ECG signal could not be analysed in case of 2 subjects due to artefacts impeding R peak detection.)…”
Section: Study IImentioning
confidence: 99%
See 3 more Smart Citations